Antiparasitic guidelines: limitations and future directions - Joachim, Anja (2025)
The revision and creation for guidelinesrequires two prerequisites, (a) the topic should attract sufficient interest tobe helpful under the current research and development topics in veterinary parasitology; b) the scientific community, specifically the WAAVP members, should be able to provide sufficient expertise in the field to put together a eam of qualified authors to write a revision or a new guideline, as well as a team of qualified reviewers to comment on the manuscript. In this context, this symposium will cover three topics: (1) a general introduction on objectives and process of developing the WAAVP Guidelines (Silvina Fernández); (2) companion animal guidelines, what we have and what we need (Anja Joachim and Angela Di Cesare); and (3) implementing the new FECRT guideline, from principles to practical application (Ray Kaplan).Objectives and process of developing the WAAVP Guidelines: The process of creating the WAAVP guidelines will be explained,highlighting the intrinsic steps and the most common difficulties encountered. Companion Animal Guidelines, what we have andwhat we need: the evaluation of efficacy of anticoccidials in dogs, parasiticides against vector-borne pathogens in dogs and cats, and anthelmintics for dogs and cats have been the subject of recent guidelines. However, the guideline for evaluating the efficacy of ectoparasiticides for companion animals should be revised next because the spectra of compounds and target parasites have greatly increased since the last edition in 2013, necessitating adaptations of the guideline. Implementing the new WAAVP FECRT Guideline,from principles to practical application: The guideline for diagnosing anthelmintic resistance using the faecal egg count reduction test in farm animals was published in 2023, since then enquiries about its use in the farm practice as well as in research have been received, thus prompting this presentation to highlight the practical application of this much needed guideline. Suggestions on revisions or new guidelines with other hosts and other parasites can be suggested and are welcome for discussion in the WAAVP Guidelines Subcommittee.